An open‐label non‐inferiority randomised control trial comparing nebulised amphotericin B with oral itraconazole in patients with pulmonary aspergilloma. Issue 9 (20th June 2021) - Ray, Animesh; Manikanta, Jagdeesh; Singh, Komal; Gabra, Pavan; Vyas, Surabhi; Singh, Gagandeep; Xess, Immaculata; Sethi, Prayas; Meena, Ved Prakash; Soneja, Manish; Sinha, Sanjeev; Wig, Naveet; et al.
Abstract: Background: Pulmonary aspergilloma (PA) is a common complication seen in patients with pulmonary tuberculosis sequelae. Antifungal therapy, including oral azoles, is commonly used though only surgical resection offers curative benefit. Local administration of amphotericin B, like intracavitary instillation, has been effective in aspergilloma patients though nebulised amphotericin B (nAB) has never been formally assessed. Objective: The aim of this prospective, non‐inferior, open‐label, randomised control trial is to evaluate the efficacy and safety of nebulised amphotericin B compared to oral itraconazole therapy in the treatment of PA. Patients/Methods: Diagnosed cases of PA (n=33) were randomised into the control group receiving oral itraconazole (n=18) and intervention group receiving nebulised amphotericin B ( n = 15). Response to treatment was assessed both clinically and radiologically at the end 6 months. Results and Conclusion: The number of patients showing overall improvement at the end of 6 months in the control arm(oral itraconazole) vs intervention arm(nebulised amphotericin B) was 65% (95% CI 38.3–85.8) and 67%(95% CI 38.4%–88.2%), respectively, in the intention‐to‐treat and 79% (95% CI 49.2%–95.3%), and 65% (95% CI 38.4%–88.2%), respectively, in the per‐protocol analysis. While there was no statistically significant difference between the intervention and control arm in both the analyses, non‐inferiority was shown in the per‐protocol but not in the intention‐to‐treat analysis. No major adverse events were noted in either group; however, a significant proportion of patients receiving nAB reported minor cough (40%), which, however, did not lead to discontinuation of therapy in any patients. Nebulised amphotericin B can be an effective therapeutic option for pulmonary aspergilloma patients.